Negotiating financial agreement in East Asia - Pitakdumrongkit, Kaewkamol Karen (Routledge, 2021)
Every international negotiation bears a risk of collapse, as even among like-minded countries, different players often have different priorities and interests. This can result in conflict as states clash over certain agreement details, and their disputes can escalate and founder the entire negotiation, missing an opportunity to realize potential initiatives. However, other circumstances have witnessed the cases of successful deals. This begets a puzzle: What did these states do to salvage their talks and seal their deals?.